Phytochemical screening and assessing the bioactive constituents of Lepisanthes tetraphylla (vahl) radlk through GC-MS analysis - Sudha Kesavarthini P; Rani S; Vishwanath B A (Journal of Global Pharma Technology, 2019)
The present study was carried for the preliminary phytochemical analysis of the ethanolic extract of the plant Lepisanthes tetraphylla (vahl) radlk belongs to the family Sapindaceae. Bioactive constituents in the ethanolic extract of Lepisanthes tetraphylla was analysed by GC-MS analysis. Phytochemical screening revealed the presence of carbohydrates, proteins and amino acids, saponins, tannins, flavonoids, gums. In GC-MS analysis, around one hundred and seventeen compounds were present, in which many compounds where not reported for their biological properties. The presence of various bioactive compounds confirms the application of Lepisanthes tetraphylla for various diseases by traditional use.